The efficacy and safety of lignocaine-embedded dissolvable microneedle versus EMLA for topical analgesia in adults undergoing venepuncture: A single-centre, parallel-group, double-blind randomised clinical trial protocol in a tertiary care setting - Muhammad Irfan Abdul Jalal; Mun Yin Yen; Lam Chenshen; Mae-Lynn Catherine Bastion; Chua Xin Yun; Sharipah Salwa Abdul Razak; Sharmilah Kuppusami; Arifah Syahirah Abdul Rahman; Mohd Eusoff Azizol Nashriby; Nurul Ashikin A. Rahim; Poh Choon Ooi; Muhamad Ramdzan Buyong; et al. (PLoS ONE, 2025)
Venepuncture-associated pain is a major source of distress commonly experienced by adult patients in day-to-day clinical practice. Topical lignocaine application before venepuncture may address this issue, but this delivery approach may be suboptimal. Hence, we aim to investigate the safety and efficacy of a novel lignocaine-embedded transdermal microneedle array patch (LEMAP) in facilitating transcutaneous lignocaine delivery to reduce procedural-related pain in adults undergoing venepuncture in a tertiary-care outpatient clinic setting. This is an investigator-initiated, single-centre, active-controlled, double-blind, randomised superiority trial divided into two distinct stages. Twenty (single-group LEMAP recipients) and 144 adult patients (72 per group; randomised to either LEMAP (intervention) or 5% EMLA patch (control) applied on antecubital fossa, near the venepuncture site, for 30 minutes) aged 18 years and above requiring routine venepuncture will be recruited from the Ophthalmology Outpatient Clinic, Hospital Canselor Tuanku Muhriz, for stage I and II of this trial, respectively. For the stage I trial, the safety endpoints are lignocaine’s pharmacokinetic parameters and clinical adverse events. In the stage II trial, the primary endpoints are the venepuncture-associated pain experience, which will be evaluated using the Visual Analogue Scale (VAS) and the skin conductance algesimeter index (SCAI) scores at one-minute post-venepuncture. Non-linear mixed-effect model and multiple linear regression will be used to analyse the stage I and II trial outcomes, respectively. The trial protocol has been registered with the clinicaltrial.gov registry (ID: NCT05694858) and adheres to the SPIRIT 2025 reporting guideline. All trial participants will provide written informed consent, which the trial investigators will obtain before trial enrollment and randomisation. The trial findings will be disseminated via peer-reviewed publications and presentations at international conferences and shared with participants via the web-based trial notification system..